GLOBAL AND PERMANENT PEACE: ILLUSION OR REALITY? - Borš, Vanja (Problems / Problemos, 2017)
The intention of this article is to problematize a possibility of establishing a global and permanent peace. As the basic starting point, that is, as the precondition of an achievement of such a form of human existence, I propose postconventional morality, which is reached by only a small number of people in their moral development. In that context, in this article, conditions and possibilities for stimulating a wider development, that is an achievement of such a form of morality, by the system of higher education will be considered. However, the starting point is that such an achievement is not possible with the form of education dominant today, but rather with the education that emphasizes some specific and unique value of philosophy, and anthropology as well. In any case, it is postconventional morality which is a precondition of a genuine (transcultural) understanding of the golden rule and the conduct in accordance with it, that is, being according to universal ethical principles.